Teaching Machines on Snoring: A Benchmark on Computer Audition for Snore Sound Excitation Localisation - QIAN, Kun; JANOTT, Christoph; ZHANG, Zixing; DENG, Jun; BAIRD, Alice; HEISER, Clemens; HOHENHORST, Winfried; HERZOG, Michael; HEMMERT, Werner; SCHULLER, Björn (Archives of Acoustics, 2018)
This paper proposes a comprehensive study on machine listening for localisation of snore sound excitation. Here we investigate the effects of varied frame sizes, and overlap of the analysed audio chunk for extracting low-level descriptors. In addition, we explore the performance of each kind of feature when it is fed into varied classifier models, including support vector machines, $k$-nearest neighbours, linear discriminant analysis, random forests, extreme learning machines, kernel-based extreme learning machines, multilayer perceptrons, and deep neural networks. Experimental results demonstrate that, wavelet packet transform energy can outperform most other features. A deep neural network trained with subband energy ratios reaches the highest performance achieving an unweighted average recall of 72.8% from four types for snoring.